Multisite replication in SLA research: attention to form during listening and reading comprehension - Morgan-Short, Kara; Marsden, Emma; Heil, Jeanne; Isa, Bernard I.; Mikhaylova, Anna; Mikołajczak, Sylwia; Moreno, Nina; Leow, Ronald P.; Slabakova, Roumyana; Szudarski, Paweł (Wiley, 2018)
We conducted a multi-site replication study with aspects of pre-registration in order to explore the feasibility of such an approach in second language (L2) research. To this end, we addressed open questions in a line of research that has examined whether having learners attend to form while reading or listening to a L2 passage interferes with comprehension (VanPatten, 1990; Leow, Hsieh, & Moreno, 2008). Our results are consistent with findings from the specific paradigm that we replicated (i.e., Leow et al., 2008) in that no effects were detected in analyses conducted over all sites. However, further investigation is warranted due to site-specific effects and methodological limitations. We found all aspects of the multi-site registered replication approach to be useful, although the registration component itself appears to be a more feasible and useful first step in order to increase the robustness and generalizability of findings in our field.